Phraseological Units Denoting Feeling and Emotions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the world of phraseological units, focusing specifically on those that denote feelings and emotions. Phraseological units, or idioms, are essential elements of language that encapsulate complex emotions and cultural nuances in succinct expressions. The article explores the meanings, origins, and usage of various idioms such as "over the moon," "down in the dumps," and "green with envy," providing insights into their metaphorical richness and cultural significance. Understanding these units enhances linguistic skills and deepens appreciation for the English language's expressive capabilities.